EFFECT OF ELEVATED TEMPERATURE ON SOME FUNCTIONAL BACTERIA IN GROUNDNUT (ARACHIS HYPOGAEA L.) RHIZOSPHERE AT DIFFERENT PHENOLOGICAL STAGES - SWETA KACHHAP; ANITA CHAUDHARY; S. D. SINGH (The Bioscan, 2015)
The present study was conducted to study the impact of elevated temperature in the present and future climate change scenarios on some functional bacterial populations in Groundnut (B-95) rhizosphere. Rhizosphere soil samples were collected and numbers of bacteria involved in nitrogen-fixing, phosphate-solubilizing and potassium- dissolving were measured with cultivation-dependent approaches. +2-3°C elevated temperature conditions from germination to maturity affected the functional bacterial populations in rhizosphere soil positively with 7.02%, 6.61% and 3.0% increase in NFB, PSB and PDB respectively at complete flowering compared to the ambient which could be positively correlated with various growth parameters (p ≤ 0.05). The current finding suggested that the elevated temperature throughout the crop growth was found to be having positive effect on the numbers of functional bacteria in groundnut rhizosphere.